(3TQM eKdK bWQHs - (3SYO GdOjf GdHGQRis; (3CHj Ydj Hf CMeO Hf GdeSJfjQ, bWQH,J (B206 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdHGQ GdQGRb Gdegjef GdZaGQ hHYO JSdjei Ydi NjQ fHj CfXe ai eKdKGJ bWQH CQLhRI dPjPI ai GdeTQH JQhb ai eSGeY GdfXGQ s
(3BNQgG (B:s
(3Ke GdHdGO GdCgdGH aGdbQG hZjQ GdEgdGJ aGdHQGQ Je GdcJGH GdeYQha agh GdbSW jahM WjH fTQg ai GdfGQ Je TQM eKdK bWQH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG NWHIs
(3efXheI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GddZIs